Chesterton, as seen by his contemporaries - Clemens, Cyril, 1902-1999; Bentley, E. C. (Edmund Clerihew), 1875-1956; Massaguer, Conrado Walter, 1889-1965 (Salt Lake City, UT : Project Gutenberg, 2025)
"Chesterton, as Seen by His Contemporaries" by Cyril Clemens is a biographical account written in the early 20th century. The book compiles memories and reflections from various acquaintances and contemporaries of the influential writer G. K. Chesterton, showcasing his character, intellect, and artistic contributions. It aims to illustrate the impact Chesterton had on those who knew him personally, revealing his distinctive personality and the admiration he generated among his peers. The opening of this work presents a rich tapestry of reminiscences from Chesterton's formative years, focusing particularly on his school days. His friends describe him as an unconventional boy, deeply engaged in literature and artistic pursuits while seemingly disinterested in the typical social activities of his peers. Although not academically distinguished, Chesterton emerged as a natural leader within a small group dedicated to debating and intellectual discussion, illustrating qualities that would define his later life as a notable writer and thinker. As the memories unfold, they capture the essence of Chesterton's early character, his distinct sense of humor, and the beginnings of his literary journey, setting the stage for an exploration of his life and legacy. (This is an automatically generated summary.)
Release date is 2025-01-21
Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Chesterton, G. K. (Gilbert Keith), 1874-1936; Authors, English -- 20th century -- Biography; Chesterton, G. K. (Gilbert Keith), 1874-1936 -- Contemporaries